(untitled) (Research, Society and Development, 2022)
This article is a cut of a research being developed in the Master’s degree program in Teaching of Sciences and Humanities - PPGECH/UFAM, and presents the result of one of the objectives proposed in the study which is to analyze the perception of teachers about the need for continuing education facing the challenges of using digital technologies in teaching practices in emergency remote education. The study involved 7 (seven) teachers from the Federal Institute of Education, Science and Technology of Amazonas - IFAM, Campus in the city of Humaitá. Data were collected by means of a GoogleForms form. The results indicate that the search for continuing education for the performance in the context of remote teaching motivated by the need to use technological resources in online classes was a demarcating point for the development of the pedagogical practices of teachers participating in the research who, on their own initiative, participated in events, courses and lectures to solve or minimize their needs in a short period of time. However, it was also evident that traditional teaching still persisted on the part of those who were resistant to a new way of being and doing education in the context of remote teaching.